2021
DOI: 10.3389/fped.2021.697091
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Outcomes of Young Children Born to HIV-Infected Mothers: A Pilot Study

Abstract: Introduction: Over 15 million children who were exposed to HIV perinatally but uninfected (HEU) are alive globally, and they are faced with multiple risk factors for poor neurodevelopment. While children who are HIV-infected (HIV+) appear to have worse neurodevelopmental scores compared to children unexposed and uninfected with HIV (HUU), the evidence is mixed in children who are HEU. This small descriptive pilot study aimed to compare neurodevelopmental scores of children who are HIV+, HEU, and HUU in Kenya.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…Others made substantive modifications by providing more specific recommendations on how to engage in responsive play and communication activities and creating a structured curriculum to guide delivery agents in their interactions with caregivers. For example, seven studies explicitly reported making substantive modifications to the play and communication activities of the CCD package (( 24 ) [Indonesia]; ( 25 ) [Mozambique], ( 26 ) [Tanzania]; ( 27 ) [Malawi]; ( 28 ) [Kenya]; ( 29 ) [India and Pakistan]; ( 17 ) [Pakistan] 5 ). In Malawi, this consisted of modifying play and communication activities to focus on touch, hearing, and other senses for children with visual impairments ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Others made substantive modifications by providing more specific recommendations on how to engage in responsive play and communication activities and creating a structured curriculum to guide delivery agents in their interactions with caregivers. For example, seven studies explicitly reported making substantive modifications to the play and communication activities of the CCD package (( 24 ) [Indonesia]; ( 25 ) [Mozambique], ( 26 ) [Tanzania]; ( 27 ) [Malawi]; ( 28 ) [Kenya]; ( 29 ) [India and Pakistan]; ( 17 ) [Pakistan] 5 ). In Malawi, this consisted of modifying play and communication activities to focus on touch, hearing, and other senses for children with visual impairments ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…These beneficiaries mostly came from low socioeconomic backgrounds. Nine studies specifically targeted vulnerable groups: children born prematurely or with low birth weight (( 40 ) [Dominican Republic]), children with visual impairments (( 27 ) [Malawi]), children with other physical and/or cognitive disabilities (( 40 ) [Dominican Republic]; ( 41 ) [El Salvador], ( 42 ) [Peru]; ( 31 ) [India]), children of HIV+ mothers (( 43 ) [Malawi]; ( 28 ) [Kenya]), children of incarcerated mothers (( 44 ) [Paraguay]), and children of HIV+ mothers experiencing antenatal depressive symptoms (( 39 ) [South Africa]).…”
Section: Resultsmentioning
confidence: 99%
“…15 Using data from our pilot study of children who were HEU (n=74) and HUU (n=74), a potential difference existed between these groups in the language domain. 41 While the difference was not statistically significant, these data were helpful for estimating our proposed sample size. Using the Bayley-3 language composite scores of this study, children who were HEU had a mean score of 73.4 (SD 13.7) and children who were HUU had a mean score of 76.3 (SD 12.7).…”
Section: Sample Sizementioning
confidence: 92%
“…Using the Bayley-3 language composite scores of this study, children who were HEU had a mean score of 73.4 (SD 13.7) and children who were HUU had a mean score of 76.3 (SD 12.7). 41 Using an average SD of 13.2, the resulting effect size is 0.22 standardised difference between means (ie, Cohen's d) for continuous neurodevelopment outcomes. With a 0.22 effect size, an alpha of 0.05 and 80% power, the estimated sample size needed is 326 per group.…”
Section: Sample Sizementioning
confidence: 99%
“…Rodriguez et al [1] report on the use of the Bayley Infant Neurodevelopmental Screener (BINS) to identify infant outcomes in five domains: cognitive, receptive language, expressive language, fine motor, and gross motor in their manuscript entitled ‘Prevalence of neurodevelopmental delays in infants with perinatal HIV infection in comparison with HIV exposure in rural South Africa’ [1]. Many studies have reported on increased risk of delayed or poorer neurodevelopmental outcomes among children living with HIV, as well as those with fetal exposure to HIV, and increasingly maternal antiretroviral treatment, who remain HIV-uninfected [2–4]. In the highest burden HIV settings, health system constraints preclude the use of lengthy, in-depth assessments of children living with HIV and those HIV-exposed uninfected (HEU) to identify those in need of additional support to reach their fullest developmental potential.…”
mentioning
confidence: 99%